COVID-19 and Social Sciences - Ferreira, Carlos Miguel; Serpa, Sandro (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The COVID-19 pandemic is having profound effects on all dimensions of life: individual, social, cultural, and public and economic health, among others. The contribution of social sciences is very relevant in understanding this disease and pandemic as well as its effects. It is also relevant for taking measures, such as, for example, compliance with physical distance, mask-wearing, no gatherings, and information to the population in a more efficient way. This book discusses topics such as COVID-19 in a risk society and its implications; the situation of patients with diabetes in a lockdown context; the technological, pedagogical, and social challenges posed by remote teaching; and, finally, the explanation of potential contributions of several specific social sciences that can shape both the taking of measures and their fulfilment in the desired direction. The book concludes with an analysis of the underlying social, psychological, and philosophical issues that are pandemic-related and that may have a considerable impact on societies and individuals, also highlighting the situation of the most disadvantaged groups, given that pandemics tend to accentuate social inequalities.